Utilization of ClassPoint Interactive Media on Organic Chemistry Course - Lestari*, Ira; Muharini, Rini; Utami, Nurzam Indah; Fatmala, Fatmala (Jurnal IPA & Pembelajaran IPA, 2024)
This research focuses on utilizing ClassPoint interactive media in learning organic chemistry courses. Interactive media can potentially increase student engagement and understanding of complex material. Organic chemistry is often considered difficult, and students rely on lecturers to understand it. However, the lack of student involvement in the learning process is a problem that needs to be addressed. This research aims to describe student perspectives on the use of ClassPoint in learning organic chemistry, evaluate the effectiveness of ClassPoint in increasing student engagement, and identify the interactive features that students are most interested in. The research involved 53 participants of the Tanjungpura University FKIP Chemistry Education Study Program students who had taken the organic chemistry course. The research results show that the perspective of Chemistry Education students regarding the use of ClassPoint Interactive media is in the strongly agree category with a percentage of 91.55%. The strongly agree category is viewed from 3 aspects, namely the motivation and interest in learning aspect; knowledge and skills aspects; as well as the feature usability aspect, each of which received the strongly agree category. This indicates that ClassPoint interactive media is liked and wants to continue to be used in learning in organic chemistry courses. By utilizing ClassPoint, students become more involved in the learning process, increase understanding, and increase motivation and interest in learning. This research is an important step in optimizing interactive learning media to support more effective and interesting learning of organic chemistry